Analytical and simulation-based prediction of surface roughness for micromilling hardened HSS - Meijer, Alexander; Bergmann, Jim A.; Krebs, Eugen; Biermann, Dirk; Wiederkehr, Petra (Technische Universität Dortmund, 2019)
The high quality demand for machined functional surfaces of forming tools, entail extensive investigations for the adjustment of the manufacturing process. Since the surface quality depends on a multitude of influencing factors in face micromilling, a complex optimization problem arises. Through analytical and simulative approaches, the scope of the experimental investigation to meet the requirements for surface roughness can be significantly reduced. In this contribution, both analytical and simulation-based approaches are presented in the context of predicting the roughness of a machined surface. The consideration of actual tool geometry and shape deviations are used in a simulation system to achieve the agreement with experimental results.
J. Manuf. Mater. Process.;3(3)
Keywords: Surface roughness prediction; Geometrical simulation; Micromilling; 620; 670